Pengembangan Pedoman in Service Training pada Kurikulum 2013 melalui KKG-PAI dalam Meningkatkan Profesionalisme Guru PAI di Kecamatan Panji Situbondo - Mahmuda , Mahmuda (Jurnal Pendidikan Islam Indonesia, 2016)
This research aims to 1) produce teacher training model in the position (In Service training) that can be delivered the PAI’s teacher to have a better understanding, implementing and enhancing competencies as the responsibility of a teacher. In order that module is easy to be used by working group of Islamic education teachers in carrying out the training. This research uses the methodology of Research and Development (RnD) that will be done by three stage. The first phase, is to identifying the learning process of teachers as a result of previous training, strengths and weaknesses as well as their effectiveness until turn up the new drafts of the model. Next, the model will be tested validation by experts, good product content experts, implementation, evaluation, design, and materials. After validation test and revision, the third stage is developing phase by limited test in the field to measure effectively how good the trainee response from observation and interview results of activities of training. To analyze the level of effectiveness product In Service training manuals, it is used an statistical analysis at pretest and posttest results as well as on the results of the post-interview training. The reseach results showed that the existence of changes after training In Service Training by using the training modules and adapt to the new one so that there is a significant difference between before use of the product with the after. It can be seen from, 1) the attitude of the teacher training after following that can carry out their obligations with ease, 2 pretest and posttest results). In the pretest measure that average 40.47 with 36 samples with a standard deviation of error levels 7.9 1.3. While the results in the measurement of unknown posttest average 67.8 with sample 36 with a standard deviation of error level 3.26 0.54. Based on these reasult it can be concluded that module is effective to used for the Working Group on Teacher Education of Islam (KKGPAI) Panji district).